S. maltophilia pneumonia: A case report - Geller, Mauro (Respir Med Case Rep, 2018)
Case report of Community-acquired pneumonia in a male patient without co-morbidities. Empiric antibiotic treatment did not resolve the clinical picture of productive cough, and a chest computerized tomography and sputum culture with antibiogram were performed, identifying S. maltophilia infection with sensitivity to levofloxacin and sulfamethoxazole/trimethoprim. Treatment with levofloxacin (500 mg/day for 15 days) resulted in resolution of the clinical picture.